Effect of Mandibular Third Molars on Anterior Crowding Assessed by CBCT - Ketenci Çay, Fatmanur (2026)
The role of mandibular third molars in the development of anterior dental crowding has long been debated, with conflicting evidence regarding their contribution. This study aimed to evaluate the effect of presence and angulation of mandibular third molars on anterior dental crowding. This study employed 138 cone-beam computed tomography scans and Little's Irregularity Index to explore the relationship between mandibular third molars and anterior dental crowding. The CBCT scans were categorized based on the third molars’ status as impacted, erupted, or absent. Moreover, impacted teeth were classified using Winter’s classification.The analysis revealed no statistically significant relationship between the presence or angulation of third molars and the severity of anterior dental crowding. These findings suggested that other factors rather than mandibular third molars may also be effective in anterior dental crowding. The results contribute to the ongoing debate by suggesting that third molars may not be the primary determinant of anterior crowding, emphasizing the need for more comprehensive research to clarify their role and the necessity of their prophylactic removal.